THE MYSTERY OF THE DROWNING OF KAN‘ĀN, THE SON OF NŪḤ: CRITICISM OF SHAHRUR’S THOUGHT - Muhammad Muhammad (ILMU USHULUDDIN, 2021)
Muḥammad Shahrur is a Muslim thinker who has many controversial works. This article describes Shahrur’s thoughts about Kan‘ān during the flash flood tragedy at the time of Prophet Nūḥ. He made a study using intertextual theory. He thought that Kanān’s drowning during the flood was because he was not the biological child of the Prophet Nūḥ, but the son of his wife’s adultery with another man without Prophet Nūḥ’s awareness. This article found Shahrur’s misinterpretation of the personality of Kan‘ān because in interpreting the verses of the Quran about the story of the family of Prophet Nūḥ, he prioritizes the intertextual’s approach with modern sciences, such as semiotics and hermeneutics, and ignores credible interpretation methods such as those are used by the scholars of interpretation, both classic and modern. Besides that, this article is a literature study that compares Shahrur’s interpretation with classical and modern scholars of interpretation.